Effect of addition graphene to ethylene vinyl acetate and low-density polyethylene - Sabet, M. (John Wiley and Sons Ltd, 2018)
Graphene (Gr) distribution in low-density polyethylene (LDPE) and ethylene vinyl acetate (EVA) considerably increased thermal stability and mechanical properties of LDPE/Gr or EVA/Gr composites. Dynamic mechanical analysis (DMA) and strength testing machine were used to study mechanical properties. The high specific surface areas and superior properties of Gr improved thermal strength, storage modulus, and mechanical properties of composites. Outstanding distribution of Grs was accomplished and verified by atomic force microscopy. LDPE/Gr and EVA/Gr composites were characterized by transmission electron microscope (TEM), X-ray diffraction, and thermogravimetric analyses to study the distribution morphology and thermal strength. Results display that the presence of filler does not create an alteration in the microscopic structure of polymers. Measurement of tensile properties shows that the tensile strength of composites contains Gr is significantly higher than similar values for pure EVA and LDPE. The DMA shows that the storage modulus of composites is much greater than that of pure EVA and LDPE. The thermal stability of the composite contains Gr is also considerably higher than that of pure EVA and LDPE. J. VINYL ADDIT. TECHNOL., 24:E177âE185, 2018. Â© 2018 Society of Plastics Engineers. Â© 2018 Society of Plastics Engineers